EFFECT OF FILLER ON STRENGTH DEVELOPMENT OF EPOXY GROUT (Malaysian Journal of Civil Engineering, 2018)
Epoxy grout is used for most structural repair works due to its high strength, adhesive and availability. This study uses epoxy resin and its hardener as binder, graded sand and ground granulated blast furnace slag (GGBFS) as filler to produce the epoxy grout. The objective is to produce a sufficient mix proportion for epoxy grout that has good workability and high strength properties, which can be used as structural repair material. The method used to obtain the mix proportion was by trial mix as determined by flowability and strength of the grout. Several batches of epoxy grouts with different epoxy: hardener: filler ratios were designed and tested for its flowability and compressive strength properties. Finally, the mix proportion with fresh properties, namely viscosity or flowability that fulfills the requirements of ASTM C 881 and has optimum strength development was selected. The optimum compressive strength obtained for epoxy grouts with 5:1:11 epoxy:hardener:filler ratio was above 70 MPa for air cured specimen, which can be considered as high strength repair material. The results for slag based epoxy grout showed that the replacement of slag up to 50% as filler to epoxy mix with proper mix proportion is suitable to be used in concrete structural repairs.